Research and application of herbal medicine in the treatment of chronic kidney disease since the 21st century: A visualized bibliometric analysis - Xu, Yunling; Chen, Jia; Wang, He; Lu, Ying (Frontiers in Pharmacology, 2022)
Background: Here, a bibliometric and knowledge-map analysis is used to analyze the research status and application of herbal medicine in the treatment of chronic kidney disease (CKD). By looking for research hotspots and key topics, we provide new clues and research directions for future research. Methods: Articles and reviews regarding herbal medicine in the treatment of CKD were retrieved from the Web of Science Core Collection (WoSCC) on May 23, 2022. The R-bibliometrix, VOSviewer, and CiteSpace software were used to conduct the bibliometric and knowledge-map analysis. Results: In total, 5920 authors at 1330 institutions from 68 countries published 1602 papers in 355 academic journals. China was the leader and pioneer in the research and application of herbal medicine in the treatment of CKD field. Beijing University of Chinese Medicine contributed the most publications. Ping Li (China-Japan Friendship Hospital) published the most articles, while Yingyong Zhao (Northwest University) had the most cocitations. However, cooperation among countries and the research institutions is not sufficient. Journal of Ethnopharmacology published the most research and application of herbal medicine in the treatment of CKD-related papers, and also was the most commonly cocited journals. The most influential research hotspots about herbal medicine in the treatment of CKD focused on diabetic nephropathy-related research, Balkan endemic nephropathy, and pharmacokinetic study. Conclusions: Herbal medicine has a wide range of pharmacological activities and therapeutic value. The research and application of herbal medicine in the treatment of CKD, especially diabetic nephropathy, will remain a hot topic in the future.